Hubungan Asupan Protein, Zat Besi dan Pengetahuan terhadap Kadar Hemoglobin pada Remaja Putri di MAN 1 Surakarta - Khatimah, Husnul, Zulia Setiyaningrum, M.Gizi (2017)
Adolescence is a period of rapid physical growth. An imbalance between nutrient intake and nutrition requirement will create nutritional problems. Iron is a major element for the formation of hemoglobin and always bind to protein in the body. Protein serve as a means of transportation of iron to the bone marrow. Lack of nutrient intake, especially iron can cause anemia. Good knowledge of anemia is the main thing in maintaining the fulfillment of iron in the daily diet. The purpose of this research was to determine the association of protein intake, iron intake and knowledge to hemoglobin level of teenage girls in State Madrasah Aliyah 1 Surakarta. This study used cross-sectional design. The number of research subject was 57 respondents, selected using proportional random sampling technique. Nutrient intake data were obtained using Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), knowledge data were obtained by using a questionnaire of 27 questions and hemoglobin level data were obtained by taking venous blood samples using SLS (Sodium Lauryl Sulfate) method. All data were analyzed using Pearson Product Moment correlation test. The results showed that protein consumption in 35 respondents (61.4%) was categorized as high intake while iron consumption of 30 respondents (52.6%) was categorized as low intake, knowledge of 37 respondents (64.9%) had moderate knowledge and 44 respondent (77.2%) was categorized as non-anemic. There is an association of hemoglobin level to protein and iron intake with p-value of 0,035 and 0,002, respectively. No association was found between knowledge and hemoglobin level (p=0,99). There was a association of protein and iron intake to hemoglobin level. There was no association of knowledge to hemoglobin level.